Analisis Proses Pengoperasian Unit Separator Produksi Minyak pada Area MPF di PT Citic Seram Energi Limited - Ahmad Al Gazali Waly; Deny Fatrianto (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The oil and gas industry requires efficient initial processing to separate reservoir fluids into oil, gas, and water phases. The Separator Unit is the main facility that plays a vital role in the surface facility production stage. This study aims to evaluate the type of separator used, identify control components, and understand the working principles and operational procedures of separators in the Main Production Facility (MPF) area. The methodology used is direct observation and literature studies during the implementation of practical work in July 2024 at PT. Citic Seram Energy Limited, Seram Non Bula Block, Maluku. The observation results show that the type of separator used is a Horizontal Three Phase Separator with tag codes 03-V-001A and 03-V-001B operating alternately. The separation process is carried out based on differences in fluid density utilizing gravity, supported by internal components such as deflector plates, mist extractors, weirs, and straightening vanes. Separator operation is maintained at an operating pressure of around 55 psig to ensure optimal separation efficiency and work safety. The conclusion of this study indicates that effective separator operation requires stable pressure and temperature control as well as routine maintenance to prevent sediment buildup and maintain product quality.